(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article explores the conceptual and methodological difficulties involved in defining and classifying literary archetypal forms. It analyzes the inherent ambiguity and multivalence of archetypes, as well as the limitations of existing typologies, including those grounded in Jungian psychology, cultural semiotics, and structuralist models. By considering alternative interpretive frameworks and recent scholarly debates, the study underscores the necessity of integrative approaches that can accommodate the dynamic, intertextual, and culturally embedded nature of archetypal patterns. The article further highlights the risks of reductionism and schematic thinking when applying archetype theory to complex literary texts